Strategy for bone metastases treatment in patients with impending cord compression or vertebral fractures: A pilot study - Rasulova, N.; Lyubshin, V.; Djalalov, F.; Kim, K. H.; Nazirova, L.; Ormanov, N.; Arybzhanov, D. (World Journal of Nuclear Medicine, 2011)
Impending spinal cord compression and vertebral fractures are considered contraindications for radionuclide bone pain palliation therapy. However, most of the patients with widespread bone metastases already have weakened vertebral segments that may be broken. Therefore, local field external-beam radiotherapy or percutaneous vertebroplasty (VP) should be considered to improve the patient′s quality of life and to institute subsequent appropriate treatment, including radionuclide therapy for bone pain palliation. The objective of this study was to develop a strategy for an effective treatment of bone metastases in patients with widespread bone metastases and intolerable pain, associated with impending cord compression or vertebral fractures. Eleven patients (5 females and 6 males, aged 32-62 years; mean age 53.8 ± 2.7 years) with multiple skeletal metastases from carcinomas of prostate (n = 3), breast (n = 3) and lung (n = 5) were studied. Their mean pain score measured on a visual analogue scale of 10 was found to be 8.64 ± 0.15 (range 8-9) and the mean number of levels with impending cord compression or vertebral fracture was 2.64 ± 0.34 (range 1-4). All patients underwent vertebroplasty and after 3-7 days received Sm-153 ethylene diamine tetra methylene phosphonic acid (EDTMP) therapy. Sm-153 EDTMP was administered according to the recommended standard bone palliation dose of 37 MBq/kg body weight. Whole body (WB) bone scan, computed tomography and magnetic resonance imaging (MRI) were performed before and after treatment in all patients. Pain relief due to stabilization of vertebrae after VP occurred within the first 12 hours (mean 4.8 ± 1.2 hours; range 0.5-12 hours), and the mean pain score was reduced to 4.36 ± 0.39 (range 2-6). Subsequent to Sm-153 EDTMP treatment, further pain relief occurred after 3.91 ± 0.39 days (range 2-6 days) and the pain score decreased to 0.55 ± 0.21 (range 0-2). The responses to treatment were found to be statistically significant (P < 0.0001). Based on the results on this limited patient population, we conclude that spinal stabilization using VP in patients with widespread bone metastases and impending cord compression is an effective way to decrease disability with pain and to facilitate subsequent systemic palliation of painful skeletal metastases by Sm-153 EDTMP therapy.
Keywords: Bone pain palliation; Sm-153 EDTMP; vertebroplasty